2022
DOI: 10.1515/nipt-2022-0005
|View full text |Cite
|
Sign up to set email alerts
|

Protection of dopaminergic neurons in hemiparkinsonian monkeys by flavouring ingredient glyceryl tribenzoate

Abstract: Parkinson’s disease (PD) is the second most prevalent neurodegenerative disease and this study underlines the significance of a small molecule glyceryl tribenzoate (GTB), a FDA approved food additive, in preventing parkinsonian pathologies in MPTP-induced animal models. The study conducted in MPTP-induced mice demonstrated dose-dependent protection of nigral tyrosine hydroxylase (TH) and striatal dopamine level by GTB oral treatment and the optimum dose was found to be 50 mg/kg/d. In the next phase, the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“…Accordingly, although induction of TBI increased glial inflammation in the hippocampus as evident by upregulation of microglial marker Iba1 and astroglial marker GFAP and increase in the expression of inducible nitric oxide synthase (iNOS), oral GTB strongly inhibited and/or normalized astroglial and microglial activation. This is consistent with our recent findings demonstrating suppression of microglial inflammation in an animal model of Huntington disease [17] and hemiparkinsonian monkeys [20] by oral GTB. Several studies have shown that TBI has a major impact on synapse structure and function via a combination of the instant mechanical insult and glial inflammation, ultimately leading to synapse loss.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Accordingly, although induction of TBI increased glial inflammation in the hippocampus as evident by upregulation of microglial marker Iba1 and astroglial marker GFAP and increase in the expression of inducible nitric oxide synthase (iNOS), oral GTB strongly inhibited and/or normalized astroglial and microglial activation. This is consistent with our recent findings demonstrating suppression of microglial inflammation in an animal model of Huntington disease [17] and hemiparkinsonian monkeys [20] by oral GTB. Several studies have shown that TBI has a major impact on synapse structure and function via a combination of the instant mechanical insult and glial inflammation, ultimately leading to synapse loss.…”
Section: Discussionsupporting
confidence: 94%
“…Oral GTB protects mice from experimental allergic encephalomyelitis (EAE), an animal model of multiple sclerosis (MS), via upregulation of TGFβ and regulatory T cells [18]. GTB also inhibits microglial activation in a mouse model of Huntington's disease [17] and a monkey model of Parkinson's disease [20]. GTB is used in the pharmaceutical industry as a safe and nontoxic additive in different dosage forms.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry was performed as described earlier [ 36 , 37 ]. Mice were perfused transcardially with 4 % paraformaldehyde and the brains kept in 30 % sucrose solution at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Glial activation including astrogliosis and microgliosis and other associated neuroinflammation participate in the pathogenesis of several neurodegenerative disorders [ 4 , 10 ], [ 11 ], [ 12 ]. Astrocytes constitute the majority of the glial cells and play a crucial role in brain homeostasis.…”
Section: Introductionmentioning
confidence: 99%